2013
DOI: 10.1212/wnl.0b013e31828250af
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer disease and risk of stroke

Abstract: Clinical diagnosis of AD is associated with considerably increased risk of stroke development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
86
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 33 publications
0
86
1
Order By: Relevance
“…28 Seventeen studies used multivariable-adjusted analysis, and 1 study used propensity score matching. 19 On a scale of 7, the overall quality of the studies was good (median score 5, range 3-6) ( Table 2). …”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…28 Seventeen studies used multivariable-adjusted analysis, and 1 study used propensity score matching. 19 On a scale of 7, the overall quality of the studies was good (median score 5, range 3-6) ( Table 2). …”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…We excluded 87 because the association of baseline cognitive impairment and future stroke was not reported, 6 because most of the participants had a history of stroke at baseline, 3 because they were duplicate reports and 1 because no adjusted estimate was reported. 17 Our final primary analysis included 18 cohort studies [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] (Figure 1). Characteristics of the 18 included studies are shown in Table 1.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations